2020
DOI: 10.1177/0091217420938896
|View full text |Cite
|
Sign up to set email alerts
|

Mental distress and need for psychosocial support in prostate cancer patients: An observational cross-sectional study

Abstract: Objective Prostate cancer is the most common cancer in German men and associated with various physical and psychosocial problems. This study investigated the association between mental distress and the subjective need for psychosocial support comparing subgroups of patients with different treatments and disease stages. Method We performed an observational, cross-sectional study including patients with four medical conditions: Active Surveillance, radical prostatectomy, biochemical relapse, metastasized disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 33 publications
2
16
1
Order By: Relevance
“…The concordance rate between the 3 screening tests was not reported. 22 In another study, Hegel demonstrated that ROC analyses showed that DT had stronger power compared to the PHQ‐9 for depression in cancer patients. The DT cutoff of 4 had a sensitivity of 100% and specificity of 45% for depression screening.…”
Section: Introductionmentioning
confidence: 99%
“…The concordance rate between the 3 screening tests was not reported. 22 In another study, Hegel demonstrated that ROC analyses showed that DT had stronger power compared to the PHQ‐9 for depression in cancer patients. The DT cutoff of 4 had a sensitivity of 100% and specificity of 45% for depression screening.…”
Section: Introductionmentioning
confidence: 99%
“…After the full-text screening, 12 studies met all criteria and were included in the review [30][31][32][33][34][35][36][37][38][39][40][41]. This included nine quantitative [30-33, 35, 39-41], one qualitative [37], and two mixed method [34,36] papers.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…The results of the quality appraisal are provided in Table 2. None of the 12 studies met all quality criteria, and only three met more than 80% of the quality criteria and were considered to be of high quality [30,34,40].…”
Section: Quality Appraisalmentioning
confidence: 99%
See 2 more Smart Citations